The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1177/0016986217690229
|View full text |Cite
|
Sign up to set email alerts
|

Rural Gifted Education and the Effect of Proximity

Abstract: Approximately 9.6 million (20%) K-12 students in the United States are enrolled in rural school districts. Rural school districts are found in every state, and while they make up 20% of the total student population, rural school districts constitute 33% of the schools in the nation. In some states, the proportion of rural school districts is as low as 6% and in others the proportion of rural districts reaches as high as 78%. In Mississippi, Vermont, and Maine, more than 50% of the students are enrolled in rura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
57
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(60 citation statements)
references
References 25 publications
2
57
1
Order By: Relevance
“…Accordingly, Greenough and Nelson nominated the Urban-Centric codes to become education researchers' standard geographic locale definition. By contrast, Puryear and Kettler (2017) questioned the Urban-Centric codes' utility for anything other than census purposes after their district-level analysis of gifted education opportunities revealed similar findings: rural-fringe districts resembled urban, suburban, and town districts more so than rural-distant and rural-remote districts. They also called for more research on the Urban-Centric codes to examine associations between opportunities and urban proximity.…”
Section: Tablementioning
confidence: 99%
See 3 more Smart Citations
“…Accordingly, Greenough and Nelson nominated the Urban-Centric codes to become education researchers' standard geographic locale definition. By contrast, Puryear and Kettler (2017) questioned the Urban-Centric codes' utility for anything other than census purposes after their district-level analysis of gifted education opportunities revealed similar findings: rural-fringe districts resembled urban, suburban, and town districts more so than rural-distant and rural-remote districts. They also called for more research on the Urban-Centric codes to examine associations between opportunities and urban proximity.…”
Section: Tablementioning
confidence: 99%
“…Using the Urban-Centric codes, multiple research teams have observed subcategorical differences within their designations of city, suburb, town, and rural for schools (Greenough & Nelson, 2015) and districts (Puryear & Kettler, 2017). Examining schools' enrollment counts and Title I eligibility rates based on the 2010-2011 Common Core of Data from the U.S. Department of Education, Greenough and Nelson (2015) stressed differences within the rural category, where 61.6% of students in rural schools truly attended ruralfringe schools (coded 41).…”
Section: Tablementioning
confidence: 99%
See 2 more Smart Citations
“…However, as this section reveals, these problems are far from universal, and some of the characteristics of rural education, such as their low student-teacher ratios, the abundance of social capital and the emergence of new technologies, open real opportunities for rural schools. In Chile, for instance, the initiative Puentes Educativos seeks to exploit the potential of multigrade teaching in rural schools for developing students' competencies like creativity, collaboration and critical thinking through changes in rural teachers' educational practices, curriculum, and educational materials (Puentes Educativos, 2018 [63]). Also several "urban" initiatives, such as alternative models based on small schools, multigrade teaching, moderate student-teacher ratios and close home-school relationships, point to the potential benefits that rural communities provide (Ares Abalde, 2014 [1]; Smit, Hyry-Beihammer and Raggl, 2015 [64]).…”
Section: Issues Shaping the Learning Experience Of Rural Studentsmentioning
confidence: 99%